Pengaruh Prenatal Gentle Yoga dalam Menurunkan Tingkat Kecemasan pada Ibu Hamil Trimester III - Eline Charla S. Bingan (Jurnal Kesehatan, 2019)
Anxiety can occur from the commitment about childbirth that will be returned and prepared for all the needs of the baby. In Malaysia, research data shows 23.4% of pregnant women experience difficulties, while in Indonesia shows 71.90% experience difficulties. The form of exercise that can help pregnant women feel comfortable during pregnancy or until the birth process is Prenatal Gentle Yoga, which is a mind processing skill, in the form of overall physical, psychological and spiritual personality development techniques that can be performed by pregnant women every day. This study aims to determine the effect of Prenatal Gentle Yoga in reducing the Anxiety Level of Trimester III Pregnant Women. The type of research carried out includes quasi-experimental research (Quasi Experiment) with a Pre and Posttest One Group Design. The sampling technique used is Purposive Sampling. The sample in this study were 31 pregnant women who were physically and mentally healthy. Data analysis conducted in this research was in the form of univariate and bivariate analysis. The results of the study have a significant effect with a p-value of 0,000 (α=0.05) which proves that there is an influence between the independent variable (prenatal gentle yoga) and the dependent variable (anxiety level) in reducing anxiety levels in trimester III pregnant women. The conclusion of this study shows that there is an influence between prenatal gentle yoga in reducing anxiety levels in trimester III pregnant women in PMB kereng bangkirai work area Palangka Raya city.